Comparative study of electrochemical wastewater treatment processes for bilge water as oily wastewater: A kinetic approach - Ulucan, Kubra; Kurt, Ugur (ELSEVIER SCIENCE SA, 2015)
In this study treatability of bilge water was investigated by electrochemical processes: electrocoagulation/electroflotation process and also the electro-fenton process as an indirect electrooxidation process. As the seawater is mixed into bilge water, the chloride content and the conductivity of bilge water are quite high, which is a great advantage in terms of electrochemical wastewater treatment. Treatability of bilge water by electrocoagulation/electroflotation process is investigated by using aluminum and iron electrodes in accordance with pH, time, temperature and current density. When the aluminum and iron electrodes are compared in electrocoagulation-electroflotation process, the results clearly showed that the aluminum electrodes were more efficient and as well as in a short period of time as 10 min. Chemical oxygen demand and oil-grease removal values obtained as 64.8% and 57% from Al and 36.2% and 12.5% from Fe, respectively. On the other hand by electro-fenton process, it was seen that higher removal efficiencies were obtained in comparison to the electrocoagulation method, with the COD and oil-grease removal being equal to 71% and 69%, respectively. The discharge standards specified by MARPOL were obtained by the electro-fenton process. When processes are analyzed in economically way, the electricity cost of electrocoagulation process by aluminum, iron and electro-fenton process was 0.54 $/m(3), 0.53 $/m(3), 0.51 $/m(3), respectively. In addition, pseudo-second-order kinetic model was fitted for both COD and Oil&Grease removal in electrocoagulation process. (C) 2015 Published by Elsevier B.V.
Keywords: Bilge water; Oily water; Electrofenton; Electrocoagulation; Electroflotation; Pseudo-first-order; Pseudo-second-order; OXIDATION; REMOVAL; COMBINATION; Chemistry; Electrochemistry